COVID-19 vaccination in India: private sector inclusion mandatory? - Rattan, Saurabh; Katoch, Vikram; Gupta, Gurdarshan; Sharma, Gopal Ashish; Sharma, Priya (International Journal Of Community Medicine And Public Health, 2022)
Background: Health services delivery system varies from country to country based on the available resources and the funding in that country. Both public and private system of health delivery work with the primary focus of providing the good health services. India has a multi-payer health care model that is paid for by a combination of public and private. Himachal Pradesh (HP) also has both public and private health institution infrastructure with penetration of public infrastructure more in the rural areas. To describe the utilization pattern of COVID-19 vaccine beneficiaries in district Kangra of HP among public and private healthcare delivery points. Method: Study was done in district Kangra with all the beneficiaries included in the COVID vaccination registered in Cowin portal. Results: Amongst the total vaccination done in dist. Kangra, 99.35% of the total doses were given in the govt setting and only 0.65% were contributed by the private setup Conclusions: Since decades most of the developing world has been struggling for healthcare access and with complex delivery systems. It becomes pertinent to note that Indian COVID-19 vaccination reached heights of success through technology driven approach reaching each and every corner of the country and crossing milestones to achieve set targets. It was not unreasonable to expect that the public sector may not be able to provide effective, sustained and uninterrupted healthcare including COVID vaccination services, which could be the reason that private health sector was also involved for the later. Dist. Kangra has worked to prove the efficacy of the public sector providing most of its vaccination through government CVCs.